Dexmedetomidine reduces acute lung injury caused by LPS through the SIRT3 signaling pathway in vivo - Chen, Jian; Cai, Yang; Peng, Xiaochun; Xu, Yuanling; Chen, Liying; Pan, Xinxin; Sun, Yingying (Frontiers in Pharmacology, 2025)
Acute lung injury (ALI) is a clinical syndrome characterized by excessive inflammatory responses. Despite the exploration of various therapeutic approaches, no effective pharmacological treatment is currently available for ALI. In the current study, we investigated the role of SIRT3 in LPS-induced ALI and the potential protective effects of dexmedetomidine (Dex), an agent that activates α2-adrenergic receptors. Histological analysis showed extensive lung damage and increased inflammatory cells in LPS-treated lung samples, with elevated TUNEL+ cells indicating apoptosis (p < 0.05). SIRT3 mRNA and protein expression were significantly downregulated following LPS treatment, both in vivo and in vitro (p < 0.05). DEX administration restored protein SIRT3 levels and reduced inflammation, while the SIRT3 inhibitor 3-TYP negated these benefits (p < 0.05). Additionally, DEX reduced pro-inflammatory cytokine levels and oxidative stress, effects that were also diminished by 3-TYP (p < 0.05). Our findings suggest that DEX exerts its protective effects against LPS-induced ALI via modulation of the SIRT3/LKB1/AMPK signaling pathway, highlighting the critical role of SIRT3 in inflammatory and oxidative stress responses in ALI.